Pengujian Tahanan Kontak dan Tahanan Isolasi PMS 150 kV Bay Penghantar Selayang 1 di Gardu Induk Paya Geli - Genhard Leonardo Situmorang; Anzila Nada Zahra; Desman Jonto Sinaga; Arwadi Sinuraya (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to evaluate the condition of the isolation resistance and contact resistance of the 150 kV Bus A Selayang 1 Conductor Separator (PMS) at the Paya Geli Substation as part of the 2 and 5 year HAR maintenance program. Insulation resistance testing was performed using a TENTECH insulation tester with a test voltage of 3 kV DC, while contact resistance was measured using a micro-ohmmeter with an injection current of 100 A in accordance with KEPDIR 0520-2.K/DIR/2014. The test results showed that the insulation resistance was in the order of hundreds of gigaohms with a leakage current of around 10⁻⁹ A, so that all phases met the minimum limit of 0.5 GΩ. The contact resistance values of 43.24 µΩ, 27.09 µΩ, and 35.90 µΩ were also below the 100 µΩ threshold with very small power loss, so that the 150 kV PMS was declared to be in very good condition and operational and supported power transmission reliability, but still required periodic monitoring and maintenance to prevent performance degradation in the future.